2013
DOI: 10.7314/apjcp.2013.14.9.5175
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Osteopontin in Patients Treated with Primary Radiotherapy for Head and Neck Cancer

Abstract: Background: The prognostic value of tumor osteopontin (OPN) in patients with squamous-cell head and neck cancer (SCHNC) was investigated. Materials and Methods: OPN expression was assessed by immunohistochemical methods in 50 patients, who were treated with primary radiotherapy (RT) for locally advanced SCHNC. The effects of OPN on clinical parameters, local-regional control after RT and metastasis-free survival, was assessed. Results: The rate of OPN expression in tumor tissue was 76%. OPN positive cases had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…A contrasting study reported a prognostic value of OPN in patients treated with primary radiotherapy for HNSCC. OPN levels increased in patients with local recurrence who were treated with primary radiotherapy for locally advanced HNSCC (Etiz et al, 2013). Changes in levels of OPN are involved in ovarian clear cell carcinoma cell invasion and it could have a crucial role in ovarian clear cell carcinoma therapy (Matsuura et al, 2010).…”
Section: Opn In Clinical Evaluationsmentioning
confidence: 99%
“…A contrasting study reported a prognostic value of OPN in patients treated with primary radiotherapy for HNSCC. OPN levels increased in patients with local recurrence who were treated with primary radiotherapy for locally advanced HNSCC (Etiz et al, 2013). Changes in levels of OPN are involved in ovarian clear cell carcinoma cell invasion and it could have a crucial role in ovarian clear cell carcinoma therapy (Matsuura et al, 2010).…”
Section: Opn In Clinical Evaluationsmentioning
confidence: 99%